Rural-urban migration trends, challenges and strategies - Rajagopalan, S. (ICFAI University Press, 2012)
"Rural-urban migration is a phenomenon that, on the one hand, reflects the dearth of employment opportunities in the rural areas and on the other, plenty of the same in the urban areas. Returns from farm activities, which dominate the rural economy, have been steadily declining in the developing countries; in non-farm activities, the returns are not much better. Employment, while being the main driver of rural-urban migration, is not the only one; in recent times, social factors, such as education and health care have also been driving rural-urban migration. While some view rural-urban migration as a problem to be addressed in terms of urban congestion, others view it as a coping strategy for the poor who seek to diversify their livelihoods. This book throws light on the phenomenon of rural-urban migration examining various perspectives on it, the global trends and challenges, and the strategies to address these challenges."